P1136Is there a negative impact of permanent pacemaker implantation in long-term outcomes after transcatheter aortic valve implantation?. (18th June 2020) - Carvalho Mendonca, T J; Patricio, L; Oliveira, M; Rodrigues, I; Portugal, G; Ramos, R; Cacela, D; Cunha, P S; Kahlbau, H; Fragata, I; Fragata, J
Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) is an established treatment in patients (P) with aortic stenosis. Despite the continuous developments of this procedure, high-grade conduction disturbances requiring permanent pacemaker (PPM) implantation is still a major and common complication of TAVI. Furthermore, long-term chronic right ventricular pacing has been associated with negative effects on ventricular function and heart failure (HF). Aim: to evaluate the long-term impact of PPM after TAVI focusing on mortality and HF hospitalization. Methods: We retrospectively examined P who underwent TAVI with a self-expanding valve from 2009 to 2018 at our institution. All P had pre-procedural clinical evaluation, including ECG, cardiac computed tomographic angiography and transthoracic echocardiography. P with previous PPM were excluded. Results: 265P (57% male, mean age 81.4 years, 20% with left ventricular ejection fraction <40%) were analysed. Mean STS score and mean Euroscore II were 6.33% and 7.07%, respectively. Mean transvalvular gradient was 52.78 mmHg and mean aortic valve area 0.67 cm2. Forty-seven P (17%) underwent PPM implantation during the first 30 days after TAVI. P requiring PPM had higher prevalence of diabetes mellitus, chronic renal disease, atrial fibrillation and right bundle branch block. During a mean follow-up of 20.3 months, post-TAVI PPM was associated with similar mortality rate (29.8% vs. 25.6%, HR 1.28, 95% CI 0.72-2.29, p = 0.42) and similar cardiovascular mortality (9.8% vs. 6.4%, HR 0.72, 95% CI 0.21-2.4, p = 0.59) compared to P without PPM. There were no significant differences in HF hospitalization (4.9% vs. 2.4%, p = 0.47). Kaplan-Meier curves of total mortality and cardiovascular mortality according to the need for PPM post-TAVI were similar. Conclusions: In P submitted to TAVI, PPM implantation is a relatively common finding, not associated with higher risk of total mortality, cardiovascular mortality or HF hospitalization in a long-term follow-up.